Expression and role of PD-L1 in colonic mucosa of ulcerative colitis patients and DSS-induced colitis mouse model - SONG Yalan; WU Tianyu; CHEN Cong; WU Zhenyu; TANG Xudong (陆军军医大学学报, 2023)
Objective To explore the role of programmed cell death-ligand 1(PD-L1) in pathogenesis of ulcerative colitis (UC). Methods A total of 29 colon tissue samples from UC patients aged 18~64 years who underwent the colonoscopy in our department from January 2022 to September 2022 were collected, and another 22 colon tissue samples from non-UC patients were also collected during the same period.The expression of PD-L1 and inflammatory factors IL-1β, IL-6, IL-17a, IL-22 and TGF-β1 were detected by immunohistochemistry and RT-qPCR.Twenty-four male C57BL/6 mice (8~10 weeks old, 23~26 g) were randomly divided into blank control group (n=4), PD-L1-Fc group (n=4), dextran sulfate sodium salt (DSS) group (n=8), and DSS+PD-L1-Fc group (n=8).The mice from the DSS group and DSS+PD-L1-Fc group were given 2.5% DSS solution for 7 consecutive days, and were changed to normal drinking water on the 8th day.The animals of the other groups were given normal drinking water.On the 3rd day, the mice in the PD-L1-Fc group and DSS+PD-L1-Fc group were injected intraperitoneally with PD-L1-Fc protein (1 mg/mL, 40 μg/animal).In 8~10 d after modeling, the expression of PD-L1 in colonic mucosa was detected, and the body weight, fecal traits, morphological changes, histopathological changes and inflammatory factors were observed in different groups. Results The expression of PD-L1 was significantly increased in the colonic mucosa of UC patients (43.03±4.044, P < 0.001) than of normal colon tissue samples, and the expression of pro-inflammatory factors IL-1β and IL-6 and anti-inflammatory factors IL-22 and TGF-β1 were increased (P < 0.05), which also existed in DSS mouse models.Intraperitoneal injection of PD-L1-Fc protein improved body weight, fecal score, gross morphology of colonic mucosa and microscopic inflammation (P < 0.05), down-regulated IL-6 and IL-17a(P < 0.05) and up-regulated IL-22 and Foxp3(P < 0.05) in the DSS+PD-L1-Fc mice when compared with the DSS group. Conclusion The upregulation of PD-L1 in UC patients and DSS-induced colitis mouse models may play an adaptive protective role.